Ispo Certification and Indonesian Oil Palm Competitiveness in Global Market: Smallholder Challenges Toward ISPO Certification - Sakti Hutabarat (Agro Ekonomi, 2017)
Certification becomes a prerequisite for tradable products to get legality and access to global market. Each tradable product can choose certificate according to its market destination. However, the application of certification standards are very low in both international (RSPO and ISCC) and domestic (ISPO) standards. This study was focused on the ISPO certification. How large is the gap between current practices and ISPO standard? What are factors that affect adoption of ISPO certification? Does ISPO deliver more access to market for oil palm smallholders? Do smallholders have adequate capacity to meet ISPO standard? These questions have been assessed and discussed in this paper to find answer and alternative way out for smallholders to meet the ISPO standard. The objective of this study is to assess capacity and willingness of oil palm independent smallholders to meet the standard of ISPO certification. This study was conducted in Pelalawan District, Riau Province using a survey method. The result shows that a number of barriers are faced by smallholders to obtain ISPO certification while the opportunity to get better access to local and global market is still uncertain. The adoption of ISPO certificate was influenced by farmers’ knowledge on agricultural practices, business  legality, household income, and land-size.